Workshop Report: Is Mathematics Inclusive or Exclusive? Putting colour, culture and context in the curriculum - Falconer, Isobel; Hunsicker, Eugenie; Johnston-Wilder, Sue; Teeluck, Vijay; Zychaluk, Kamila (MSOR Connections, 2022)
The workshop, “Is Mathematics Inclusive or Exclusive? Putting colour, culture and context in the curriculum” was held in January 2022 with the goal of supporting a national discussion around race and the mathematics curriculum in UK higher education. This report summarises the talks and discussion, which related to racial and ethnic inclusion in the history of mathematics, race and culture in mathematics education, and ethics and inclusion in mathematics. It concludes with a proposal of actions for individuals, departments and institutions and the mathematics community in UK higher education to move work on this area forward.